Letramento crítico e multimodalidade no ensino de língua inglesa: reflexões sobre um livro didático do PNLD - Hashimoto, Michelle Rie (2020)
The following master thesis reports the results of a research that sought to investigate how English textbooks approach the assumptions of multiliteracy in the construction of their activities, verifying how the meaning making is established and constructed from the union of different multimodal elements that make up the contemporary texts. Thinking about the changings resulting mainly from the technological advances, new writing technologies were incorporated into the text, changing the means of communication and interaction, highlighting the potentiality of different linguistic resource, besides the verbal one, to the meaning making process. In this perspective, it is understood that the text is much more than just what the verbal elements present, on the contrary, all the elements present in it, visual and implicit, carry meaning. Thus, language teaching must go through multimodality assumptions, considering the linguistic multiplicity of contemporary texts, as well as critical literacy, since the semiotic resources present in these texts presuppose new ways of reading and understanding the world, assuming critical and reflective characteristics. Through the theoretical contributions of Cervetti, Pardales e Damico (2001), Cope & Kalantzis (2008), Duboc (2012), Duboc e Gattolin (2015), Kress (2003, 2006, 2010), Monte Mór (2006, 2010, 2018), Menezes de Souza (2011, 2018), among others, it was discussed the multiliteracy perspective, critical literacy and multimodality. Through a qualitative approach, it intends to verify, through a documental analyses, activities of an English textbook of the first year of high school, to verify how they approach the multimodal and critical assumptions. From the analyses of the data, it was found that there are activities that follow the principals of critical literacy and multimodality, as well as activities that, although discuss important social themes and present multimodal elements for its composition, they focus, at first, only in the linguistic e structure aspects of the language. However, they present a significant expansion and exploration potential to wider readings and meaning making.